CULTIVATING SUCCESS: ENTREPRENEURIAL MINDSET PROMOTION IN INDONESIAN ENTREPRENEURSHIP EDUCATION - Endang Ruchiyat; Ricky Agusiady; Ijang Faisal (Journal of Jabar Economic Society Networking Forum, 2024)
Entrepreneurship education in Indonesia is experiencing rapid development with the aim of fostering an entrepreneurial mindset among pupils and students. However, various significant challenges still hamper the effective implementation of entrepreneurship curricula in educational institutions. These challenges include limited financial resources and competent teaching staff, lack of synchronization between the curriculum and industry needs, the influence of local cultural values that do not support innovation and independence, and lack of access to technology and innovation. To overcome these challenges, a holistic approach is needed that involves various parties, including government, educational institutions, the industrial sector and communities. Strategic efforts to overcome resource limitations include adequate budget allocation and intensive training for teaching staff. Close collaboration with the industrial sector is also vital to ensure the curriculum is relevant and provides the practical experience required by students. Additionally, entrepreneurship programs should be designed to respect and utilize local cultural values while integrating modern entrepreneurial principles. Investments in technology infrastructure and technology training programs are also needed to increase access to innovation. Evaluation and measurement of the success of entrepreneurship programs must be carried out in a structured and ongoing manner to ensure the program is effective. By implementing these strategies, it is hoped that educational institutions in Indonesia can be more effective in cultivating an entrepreneurial mindset, so that pupils and students are ready to face challenges and take advantage of opportunities in the business world. Effective entrepreneurship education will contribute significantly to economic growth and increase the welfare of Indonesian society, as well as producing a generation of entrepreneurs who are innovative and competitive at the global level.